The Problem of Human Trafficking Continues in the 21st Century - Corsei, Andreea (Acta Universitatis Danubius. Juridica, 2022)
Trafficking in human beings is a violation of individual freedoms and dignity and is a serious form of crime, and is still occurring in the 21st century. The phenomenon has major consequences on the life and health of human beings, while also a threat to the security and sustainable development of contemporary society. Trafficking in human beings is a national problem as well as a transnational threat. In the context of the globalization of contemporary society, the types and forms of manifestation of human trafficking are becoming more complex and latent. This study will address some of these, being the most common and / or caused by the often voluntary action of citizens' behavior. The paper is a theoretical approach to the phenomenon of trafficking in human beings and the fight against it in the 21st century. Among the main challenges facing actors involved in the fight against trafficking in human beings and which do not allow them to have sufficient statistics, information, results and actions are mixed flows of immigrants, insufficient level of identification of victims, fear of collaboration, barriers insufficient and the capacity of the competent staff in the field. However, the Republic of Moldova is trying to prevent and combat the phenomenon of human trafficking, which can have very diverse manifestations of evolution and depending on many factors.